New Insights on Pulmonary Paracoccidioidomycosis - Queiroz-Telles, Flá vio de; Peçanha Pietrobom, Paula Massaroni; Rosa Júnior, Marcos; Baptista, Rodrigo de Melo; Peçanha, Paulo Mendes (Seminars in Respiratory and Critical Care Medicine, 2020)
Paracoccidioidomycosis (PCM) is one of the most relevant systemic endemic mycoses in Latin American countries, especially in South American countries, with endemic and hyperendemic areas. The real burden of PCM may be underestimated because of a lack of compulsory case notification. Recent phylogenetic data revealed that Paracoccidioides brasiliensis comprises several cryptic species including P. brasiliensis and P. lutzii. However, the genetic biodiversity of Paracoccidioides does not affect the clinical manifestations or therapeutic response to therapy. Lung involvement is a common finding, especially in patients experiencing the chronic form of the disease, and, because of its similarities with tuberculosis, clinicians must be alert to the possibility of PCM in patients with chronic respiratory manifestations and epidemiological risk factors for this fungal disease.
Keywords: paracoccidioidomycosis; Paracoccidioides; environment; lungs; axial computed tomography; pulmonary sequela; itraconazole; therapy